2012
DOI: 10.1016/j.fertnstert.2012.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific spontaneous activation during mouse oocyte maturation

Abstract: Objective To examine whether spontaneous oocyte activation is determined by genetic differences and interacted with culture environment. Design Experimental Study. Setting Temple University School of Medicine. Animals C57BL/6, DBA/2, C3H/HeJ, and A/J strains, along with reciprocal F1 hybrid female mice (5–6 weeks). Intervention(s) Immature oocytes from different mouse strains were collected and cultured in different maturation conditions including different serum, serum replacement, bovine serum albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…This mode of egg activation, without Ca 2+ release, may explain the spontaneous activation observed in vivo in ovulated hamster and mouse eggs left to reside in the oviduct for extended periods of time in the absence of fertilization (Whittingham and Siracusa, 1978;Xu et al, 1997;Yanagimachi and Chang, 1961). Moreover, eggs from the C57BL/6 strain, the strain used in our studies, have been shown to have a particularly high susceptibility to spontaneous activation during in vitro maturation (Cheng et al, 2012). Thus, it is possible that a related mechanism might be responsible for the activation we observe.…”
Section: Discussionmentioning
confidence: 60%
“…This mode of egg activation, without Ca 2+ release, may explain the spontaneous activation observed in vivo in ovulated hamster and mouse eggs left to reside in the oviduct for extended periods of time in the absence of fertilization (Whittingham and Siracusa, 1978;Xu et al, 1997;Yanagimachi and Chang, 1961). Moreover, eggs from the C57BL/6 strain, the strain used in our studies, have been shown to have a particularly high susceptibility to spontaneous activation during in vitro maturation (Cheng et al, 2012). Thus, it is possible that a related mechanism might be responsible for the activation we observe.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, in contrast to zygotes obtained from old F1 and SWISS oocytes, zygotes from old C57BL/6 oocytes enter the 1st mitotic interphase faster than their counterparts from young oocytes. C57BL/6 oocytes have been reported as particularly prone to spontaneous parthenogenetic activation [ 68 ]. Although each C57BL/6 substrain may display different phenotype, it is possible that with age oocytes from our C57BL/6 substrain (C57BL/6Tar) become more susceptible to parthenogenetic activation, which can be reflected by the accelerated pronuclei formation.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the atypical and delayed pattern of Ca 2+ release, observed alongside the low number of embryos and offspring, could be spontaneous activation, unrelated to Ca 2+ release, Abbreviations: ART, assisted reproductive technology; Ca 2+ , calcium; ICSI, intracytoplasmic sperm injection; InsP 3 , inositol 1,4,5-trisphosphate; PI(3)P, phosphatidylinositol 3-phosphate; PI(5P), phosphatidylinositol 5-phosphate; PIP 2 , phosphatidylinositol 4,5-bisphosphate; PLCζ, phospholipase C zeta. which is common in some strains of mice (Cheng et al, 2012), alongside with the introduction of PLCζ knockout sperm. Indeed, eggs that had been fertilized by knockout sperm also displayed multiple pronuclei, consistent with the inability of a sufficient polyspermy block (Nozawa et al, 2018).…”
mentioning
confidence: 99%